Juozas Keliuotis in the Target of KGB in 1956–1978 - Okuličiūtė, Lina (Genocidas ir rezistencija, 2009)
The life of Juozas Keliuotis, one of the most conspicuous cultural workers of Lithuania, in Soviet times shows the specificity of the psychological pressure on intellectuals. The KGB unit in Lithuania involved many personalities in its manipulatory games. J. Keliuotis was of no exception. Persecuted and morally broken he wrote the memoirs revealing sufferings in the camp and violations of human rights. In 1962–1975, KGB spared no efforts seeking to find and obtain the memoirs of the intellectual in question. Even though the security failed to fetch the manuscripts of the intellectual, it succeeded in hindering for a long time their passing over to the West.Dealing with the independent Lithuanian authoritative persons was planned by experienced and influential KGB operational workers. In 1956–1978, J. Keliuotis was shadowed by quite a number of agents. It was people from the environment of the intellectual that were mostly hired. Most frequently he had to communicate with the agents of influence. For J. Keliuotis’ control not only agents were used, but also different ways for his efficient shadowing. KGB, with interruptions, applied various so-called operational technical measures: listened to his conversations, carried out secret searches in his apartment, made photos, and controlled J. Keliuotis’ correspondence. Due to constant and active spying by KGB, J. Keliuotis lost trust in his close people.KGB aimed at neutralizing the cultural influence of intellectuals. It was useful to discredit the authoritative persons by instigating them to be in conflict with émigré in terms of cultural relations. In 1971, J. Keliuotis spoke forcibly in the press, not only condemning the activity of emigrants, but also demonstrating economic and cultural “achievements” of Soviet Lithuania. The article of the intellectual was re-edited by operational employees in the direction useful for the Soviet system. The forced trampling on his world outlook meant the fictitious demonstration of loyalty to the Soviet regime. Moreover, such repentance in the press showed that a certain person was gripped by KGB. Public statements of intellectuals were used for Soviet propaganda, and the persons themselves who lost their authority were pushed aside. The individuality of J. Keliuotis in fighting with émigré was necessary for KGB as the tool of manipulation aimed at denying the historic truth. Nevertheless, in the eyes of the public of Soviet Lithuania J. Keliuotis remained as the enlightened person from the times of independence and the advocate of Western modern art.• Keliuotis was persecuted until his death 1983 The LSSR Supreme Court rehabilitated the intellectual on December 16, 1998. Only with the change in the political situation, persecution of persons of anti-Soviet disposition and not loyal to the Soviet system was stopped.
Keywords: KGB; political prisoners; agents; Juozas Keliuotis; propaganda